Konstrukcja skali pomiaru jakości nauczania - Borecki, Piotr; Galant, Agnieszka; Kozyra, Cyprian (The Development of Measurement Scale of Quality of Teaching, 2007)
The authors describe process of developing new measurement scale of quality of teaching at Wroclaw University of Economics. The scale was developed with aim of students interested in employing survey methodology in total quality management. Statistical methods like factor analysis, reliability analysis of measurement and linear regression were applied in this process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 129-138